A comparative study on the performance of three color schemes in landscape preference tests - Luo, Tao; Xu, Min; Wang, Zhifang; Yu, Zhaowu (Journal of Environmental Engineering and Landscape Management, 2019)
The photo color is recognised as one of the most significant but not fully understood factors influencing the results of landscape preference research. In this context, this paper compares the performances of three photo color schemes (original, rendered and white-black color schemes) frequently used in landscape preference tests to figure out which is the more suitable alternative to an original color photo. Statistics analysis results demonstrated that: 1) In general, the photo color schemes particularly the white-black scheme will significantly affect the results of landscape preference test. Compared with white-black, color in any other forms can increase the degree of preference for a given landscape. 2) The photo color scheme plays a decisive role in respondent’s judgment on some landscape attributes. Original color, White-black color and Rendered color schemes are better suited in landscape preference tests that highlight the effect of color, characteristic and naturalness respectively. 3) When the Rendered color scheme is used as an alternative to the Original color scheme, it has a much better performance than the White-black Color Scheme and is therefore recommended as the prior alternative color scheme to the Original color scheme under most scenarios in landscape preference research. Based on these results, it is suggested that color should be more carefully treated according to its different performance in landscape cognition research.